Gender differences in weight gain during attempted and successful smoking cessation on dulaglutide treatment: a predefined secondary analysis of a randomised trial - Mirjam Christ-Crain; Andrea Meienberg; Thilo Burkard; Bettina Winzeler; Fabienne Baur; Cihan Atila; Sophia Lengsfeld; Cemile Bathelt (BMJ Nutrition, Prevention & Health, 2023)
Background Women seem to have more difficulty quitting smoking than men. This is particularly concerning as smoking puts women at a higher risk of developing smoking-associated diseases. Greater concerns about postcessation weight gain in women have been postulated as a possible explanation.Methods Predefined secondary analysis of a placebo-controlled, double-blind, parallel-group, superiority randomised trial including 255 adults who smoke daily (155 women, 100 men). Participants received weekly dulaglutide (1.5 mg) or placebo (0.9% sodium chloride) in addition to standardised smoking cessation care (varenicline 2 mg/day plus behavioural counselling) over 12 weeks. We aimed to investigate gender differences in weight change after dulaglutide-assisted smoking cessation. Weight change between baseline and week 12 was analysed as absolute and revative weight change and as substantial weight gain (defined as >6% increase).Results No gender differences were observed in absolute or relative weight change neither on dulaglutide nor placebo treatment. However, substantial weight gain (defined as >6% increase) in the placebo group was almost five times more frequent in females than males (24% vs 5%). Female patients were less likely to have substantial weight gain on dulaglutide compared with placebo (1% (n=1/83) vs 24% (n=17/72); p<0.001), while this dulaglutide effect was less pronounced in males (0% (n=0/44) vs 5% (n=3/56); p=0.333).Conclusion Dulaglutide reduced postcessation weight gain in both genders and was very effective in preventing substantial weight gain, which seems to be a specific observation in females.Trial registration number NCT03204396.